Reading Tanbih Syekh Abdullah Mubarok: The Islamic Social Harmony Values in Mother Tongue - Hidayat, Angga Pusaka (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2023)
Harmony among us is one of the cores of Islamic doctrine. This paper intends to trace how Islamic teachings regarding conformity and social harmony are conveyed through the mother tongue. The values of universal Islamic harmony are articulated within the locality framework to align with the local wisdom that has previously grown in society. Islamic doctrine, especially regarding social harmony, will more easily touch ordinary people when conveyed in language and terms that are easy for ordinary people to understand. The mother tongue has brought Islamic teachings closer to the culture and life of the local people. The concept of social harmony was deliberately chosen because it reflects a desired point of social balance in the behaviour and rules of the social community. Which end of credit is constantly moving and changing. This paper chooses the focus study of Tanbih Syekh Abdullah Mubarok bin Nur Muhammad (1846-1956). This figure is an exceptionally prominent tarekat scholar in West Java.Tanbih contains his teachings and advice written in Sundanese. The position of this text is significant for students of the Qadiriyah Naqsyabandiyah Order who are affiliated with Syekh Abdullah Mubarok because Tanbih is always recited in the essential rituals of this group. There are four main ideas in Tanbih Syekh Abdullah Mubarok: harmony between religion and state, humanity, tolerance, and firmness of faith. The concept of social harmony in Tanbih continues the main principle of cageur-bageur, the perfect body-the ultimately innate. This social harmony involves urang (self) with religion and the state, urang (self) and batur (others), as well as kudu (recommendations/commands) and ulah (prohibitions) principles.